Upaya Guru Menstimulasi Perkembangan Bahasa Ekspresif Anak Usia Dini di TK Rumah Balita Pintar Kecamatan Tanjung Bintang Kabupaten Lampung Selatan - Indraswary, Yona Eby; Harianto, J.; Pamungkas, A.; Ngadimun, H. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Language development is the most important aspect of development. This aspect of development must be achieved from an early age. One of them is the development of expressive language. To achieve optimal expressive language development, all potential can be stimulated by the teacher. This study aims to describe the efforts of teachers in stimulating the development of expressive language in early childhood at the Smart Toddler House Kindergarten, Tanjung Bintang District. This research is a research using descriptive qualitative approach method. Sources of research data obtained from primary data and secondary data. The researcher obtained primary data from the results of interviews with class B teachers at the Smart Toddler House Kindergarten and observations of teachers and children regarding the development of children's expressive language. Secondary data obtained from the results of documentation in the form of photos. The data obtained is then collected, reduced, described, tested for the validity of the data and concluded.The results of the study indicated that the efforts of the teacher at the Smart Toddler House Kindergarten, Tanjung Bintang District, had developed the expressive language skills of grade B early childhood through the storytelling method using finger puppet media which was carried out optimally.